Proceedings of the 17th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2014
DOI: 10.1145/2531602.2531628
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring email to indicate project team performance and mutual attraction

Abstract: Many managers and mentors for project teams desire more efficient and more effective ways of monitoring and predicting the quality of social relationships and the performance of teams under their purview. A previous study [13] found that one form of linguistic mimicry, linguistic style matching, and some lexical features indicated team performance and mutual attraction in short-term, laboratory tasks. In this paper, we evaluate whether these measures also work as indicators for performance, shared understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…In order to test this relationship, a Cohesion measure was calculated by the LSM equation as proposed in [8]. It is important to mention that researchers who have used this measure have not found a relationship between LSM-based cohesion and performance in tasks that required virtual teams to communicate using emails [5]. Nevertheless, cohesion based on LSM has been used to show a positive relationship between cohesion and performance in chat communication settings [21], [22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to test this relationship, a Cohesion measure was calculated by the LSM equation as proposed in [8]. It is important to mention that researchers who have used this measure have not found a relationship between LSM-based cohesion and performance in tasks that required virtual teams to communicate using emails [5]. Nevertheless, cohesion based on LSM has been used to show a positive relationship between cohesion and performance in chat communication settings [21], [22].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, high group potency teams used a higher percentage of verbs related to the future category than low group potency teams. It has been reported that future-oriented words can be be linked to performance indicators [5]. Thus, it is possible that high potency teams tend to use more future verbs because they are more focused on the project's tasks.…”
Section: Features Related To High-level Group Potencymentioning
confidence: 99%
See 1 more Smart Citation
“…This particular study tested the LSM measure using chat communications generated during a one-hour session from single gender teams. However, researchers who have applied LSM to the analysis of email messages among team members over an extended period of time were unable to duplicate the significant relationship between cohesion and performance [23].…”
Section: Related Work On Cohesion Measuresmentioning
confidence: 99%
“…The monitoring of communication channels in a way in which information is visible to others may impact how such technologies may be adopted (Munson, Kervin, & Robert Jr, 2014), and awareness must be considered in the context of its use (Abowd, Dey, Brown, Davies, Smith, & Steggles, 1999). Providing feedback from automated sharing is important, and should also provide the ability for users to control the sharing in the meantime, to reduce anxiety related to over-sharing information (Patil, Schlegel, Kapadia, & Lee, 2014).…”
Section: Privacymentioning
confidence: 99%